Keberhasilan Inisiasi Eksplan KEBERHASILAN INISIASI EKSPLAN TUNAS DAN DAUN GMELINA (Gmelina arborea L.) DENGAN PENERAPAN BERBAGAI METODE STERILISASI - Wulandari, Arum Sekar; Sandra, Edhi; Dian Kirani, Annisa (Journal of Tropical Silviculture, 2025)
Gmelina is a fast growing species that has high sufficient economy value and useful as medicinal plant. Propagation of gmelina by tissue culture has not been widely applied in Indonesia. This study aims to analize the effect of explant types and sterilization methods on the success of gmelina initiation. Treatments used in this study are explant types (apical shoot and leaf) and four sterilization methods (B1-B4) using detergent, tween 80, fungicide, bactericide, NaOCl, and HgCl2. All sterilization methods can produce 6‒19% sterile gmelina shoot culture, but has not succeded producing sterile gmelina leaf culture. Contamination by fungi and bacteria is the main cause of failed gmelina shoot and leaf culture initiation. In general, sterilization methods used in this study has succeeded in eliminating microbes on the explant’s surface, but has not succeeded in eliminating microbes inside the explant.